19 Recurrent myocardial infarction is an independent predictor of cognitive decline in older patients with non-ST elevation acute coronary syndrome: a prospective cohort study. (June 2018) - Gu, Sophie Zhaotao; Batty, Jonathan; Veerasamy, Murugapathy; Sinclair, Hannah; Edwards, Richard; Das, Rajiv; Zaman, Azfar; Egred, Mohaned; Ahmed, Javed; Purcell, Ian; Bagnall, Alan; Spyridopoulos, Ioakim; et al.
Abstract : Background and objective: Dementia is a growing health burden of an ageing population. There are no previous studies evaluating cognitive impairment in older patients with non-ST-elevation acute coronary syndrome (NSTEACS) undergoing invasive care in the setting of an ageing population. This study aims to evaluate the prevalence of cognitive impairment (CI) and the predictors of cognitive decline at 1 year in this high-risk older NSTEACS patient group. Methods: Patients with NSTEACS, aged 65 years and referred for urgent coronary angiography±percutaneous coronary intervention (PCI), were recruited into the study to Improve Clinical Outcomes in high-risk patients with acute coroNary syndrome (ICON-1). The current analysis is a substudy of ICON-1. Cognitive assessment was examined using the Montreal Cognitive Assessment (MoCA) score. The composite major adverse cardiovascular events (MACE) comprised death, myocardial infarction (MI), unplanned revascularisation, stroke and significant bleeding at 1 year. Results: Of 298 patients, 271 had cognitive assessment at baseline, and 211 had follow-up MoCA assessment at 1 year. Median follow-up was 366 days (inter quartile range [IQR] 10). The mean age of study participants was 80.4±4.8 years; 170 (62.3%) were male. There was a high prevalence (n=130, 48%) of cognitive impairment at baseline. Patients with CI experienced higher MACE rates at 1 year (30.2% vs 19.9%, p=0.049) compared to normal cognition patients. There is a significant reduction in overall MoCA score from baseline to 1 year follow-up (mean reduction in score: 0.6±3.3, p=0.007, see figure). Seventy-four (35.1%) patients experienced cognitive decline (MoCA score drop by 2 points) at one-year. Decliners were more likely to be frail. Recurrent myocardial infarction was an independent predictor of cognitive decline at 1 year (Odds Ratio [OR] 3.34, 95% Confidence Interval [95% CI] 1.22–9.15, p=0.02) after adjustment of age and sex in multivariate analysis model. Conclusions: In older patients undergoing invasive management of NSTEACS, there is a high prevalence of cognitive impairment at baseline. Recurrent myocardial infarction is independently associated with cognitive decline at 1 year. Clinical Trial Registration- http: //www.clinicaltrials.gov Unique identifier: NCT01933581 .